Matemática no projeto Escola Integrada: distanciamentos e aproximações entre as práticas das oficinas e as práticas da sala de aula - André Augusto Deodato (2012)
In this qualitative research we aim to present distances and approximations made by students in an extended-time school project betweenthe mathematics classroom practice and the practices in some mathematics workshops. We have followed a fifth grade class of an Elementary School whose extension-time occurs through the Projeto Escola Integrada (PEI). Participant observation wasthe main resource to collect empirical material for this study. The empirical material is constituted of the transcripts of students interactions, produced from the records of observation and from audio and video recording of the activities made bythe students in the mathematics workshops and in the mathematics classroom. We make use of a theoretical framework which includes authors from the fields of Mathematics Education, Anthropology and Public Policy related to the expansion-time schools. For the development of the analysis, we have relied on authors who emphasize the relationship between social practice and learning, in a situated perspective. By analyzing the practices in the classroom and in theworkshops, we identified distances and approximations between them, made by the students, which are presented by five categories: students participation, the use of language, the reorganization of time and space at school, oscillation in the roles of students and teachers and the use of the mathematical content. We identified distances between the forms of participation of the students, as we noticed that some of them participated discreetly in the classroom practice while they showed an outstanding participation in the workshops. We also found distances regarding the use of language by students, as they tended to communicate using a formal language in the classroom and using a more colloquial language in the workshops. In addition, the different organization of space and time in the investigated practices contributed for the students to distance them. On the other hand, we realized that students understood more clearly the role that the teacher and themselves should play in the classroom, while in the workshops such roles seemed to oscillate, sometimes approximating, sometimes distancing from the role of the student and of the teacher in the classroom. Finally, from the workshops involving mathematical notions of graphs and tables, symmetry, probabilityand number system, we could notice that in some situations the students made approximations and in others they put distances between workshops mathematics and classroom mathematics.